Physico-chemical characterization and in vitro inflammatory and oxidative potency of atmospheric particles collected in Dakar city's (Senegal). (February 2019) - Ndong Ba, Awa; Cazier, Fabrice; Verdin, Anthony; Garcon, Guillaume; Cabral, Mathilde; Courcot, Lucie; Diouf, Amadou; Courcot, Dominique; Gualtieri, Maurizio; Fall, Mamadou
Abstract: Exposure to atmospheric pollutants has been recognized as a major risk factor of respiratory and cardiovascular diseases. Fine particles (PM2.5 ) and a coarser fraction (PM>2.5 ) sampled at an urban site in Dakar (HLM), characterized by high road traffic emissions, were compared with particles sampled at a rural area, Toubab Dialaw located about 40 km from Dakar. The physicochemical characteristics of samples revealed that PMs differ for their physical (surface area) and chemical properties (in terms of CHN, metals, ions, paraffins, VOCs and PAHs) that were 65–75% higher in urban samples. Moreover the fine PMs contain higher amounts of anthropogenic related pollutants than the PM>2.5 one. These differences are sustained by the ratios reported for the analysed PAHs which suggest as predominant primary emission sources vehicle exhausts at urban site and biomass combustion at the rural site. The inflammatory response and the oxidative damages were evaluated in BEAS-2B cells by the quantification of 4 selected inflammatory cytokines (TNF-α, IL-1β, IL-6, IL-8) and of total carbonylated proteins and the oxidative DNA adduct 8-OHdG after 8 or 24 h exposure. In accordance with the different sources and different physical and chemical properties, the inflammatory response and the oxidative damages were found higher in bronchial cells exposed to urban PMs. These data confirm the importance, also for West African countries, to evaluate the correlation between PM physico-chemical properties and potential biological impacts. Graphical abstract: Highlights: Urban and rural PM chemical and physical composition is reported. Both fine and coarse PM induced inflammatory responses. Fine PM emission sources are defined. Urban PM was more inflammogenic than rural PM. Both fine and coarse PM induced oxidative damages. Abstract : Dakar air pollution, influenced by anthropogenic activities, causes inflammatory responses and oxidative damages in vitro .